Manajemen Pelayanan Unit Pelaksana Teknis Dinas (UPTD) Kesehatan Puskesmas Kecamatan Siak Kecil Kabupaten Bengkalis - ", Febriandi; Khairani, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract: Technical Implementing Service Management Department (UPTD) Health Clinics in the Siak Kecil District Bengkalis Regency. Implementing Technical Service Unit (UPTD) Health Clinic is the only Siak Kecil Subdistrict health centers in the districts of Siak Kecil and is one of the agencies that provide health care services to the community in Bengkalis District in General and Siak Kecil in particular. The purpose of Implementing Technical Service Unit established (UPTD) Health Clinics of Siak Kecil District is "to meet the needs of the Ministry of public health are located in the Sub-District of Siak Kecil".On the implementation of the administrative service of the technical Office of the implementing Units (UPTD) Siak Kecil Subdistrict health centers Health hasn't been able to implement an optimal service system and have not been able to give satisfaction to the patient. While the Siak Kecil is the only Clinics Clinics in Siak Kecil so that Technical Implementing Agency (UPTD) Health Clinics in Siak Kecil District became the object of Siak Kecil Sub-district in community healthcare. The most important activities in Implementing the Technical Service Unit (UPTD) Siak Kecil is a Subdistrict health centers Health serve patients in various forms of quality services which are based on the implementation of decisions of the Minister of health of the Republic of Indonesia Number 828/MENKES/SK/IX/2008 about the minimum service standard health.The purpose of this research is to know the management of the Ministry in Implementing Technical health services Clinics Sub Regency of Bengkalis and Siak Kecil to know what factors are affecting the management of the Ministry, the concept used in the theories put forward Ahmad Farich (2011: 45-57) that reveal the Health Ministry Mananjemen consists of planning, organizing, monitoring, supervision and assessment work on this research used a qualitative research method discriptive, this research was done in Implementing Technical Service Unit (UPTD) in Siak Kecil Subdistrict health centers health data gathering researchers use techniques of observation, interview and documentation.The results of this research indicate that in providing services to the community in the executing unit of the employees of the Technical Services (UPTD) Health Clinics in Bengkalis Regency of Siak Kecil District Management of existing Services do not meet the standards set. This is because the service employees in Implementing Technical Service Unit (UPTD) Health Clinics the Bengkalis District Siak Kecil District are still using manual systems and computerization has not used. Still often occurs in queue provides services to the community so that the management of the Ministry in Implementing the Technical Service Unit (UPTD) Siak Kecil subdistrict health centers Health District Bengkalis has not been optimal.Keywords: Management, Services, Siak Kecil Sub-District